Ley De Transparencia Y Su Impacto En La Gestión Social Del Municipio De Quevedo, Periodo 2022-2023 - Buenaño Alvarez, Josué Alexander (2025)
This study assesses the impact of the Organic Law on Transparency and Access to Public Information (LOTAIP) on the social management of the Municipality of Quevedo (2022–2023), examining how the official disclosure of data influences active transparency, citizen participation, and perceptions of the effectiveness of social programs. A quantitative, descriptive, and documentary approach was employed: a structured questionnaire of 16 closed-ended questions was administered to a randomly selected, representative sample of citizens over 18 years of age. The survey explored the frequency and channels of information access, the degree of involvement in municipal planning, evaluations of program quality and impact, and suggestions for improvement. Simultaneously, legal obligations (LOTAIP, the Constitution, and the COOTAD) were compared with the content of the GAD Quevedo’s web portal. Anticipated findings indicate a gap between data publication and its effective reception, demonstrating that passive transparency does not translate into genuine active transparency. It is expected that participation in planning will range from moderate to low and that satisfaction with social programs will be limited, owing to the absence of clear performance indicators. Furthermore, citizens are predicted to advocate for the integration of digital tools, regular audits, and hybrid dialogue forums to enhance governance. These insights support a shift toward an Open Government model that combines proactive dissemination, real-time information systems, regular auditing, and civic education, aiming to bridge these gaps and reinforce institutional legitimacy in Quevedo.